THE ORIGIN OF THE DEPRESSION LAKE SYSTEMS TENIZ NORTHERN KAZAKHSTAN - N.V. Nazarova,; P. Dmitriyev,; N.P. Beletskaya,; M.M. Taizhanova,; M.D. Kulchikhan, (Academic Journal of Physical and Chemical Sciences, 2019)
The article discusses the origin of the system of peculiar lake basins of Northern Kazakhstan, called tenis - steppe seas, due to the vast areas. With deep incision of the basins of the shadows, so that the water level marks in them are below the edge in the Irtysh channel at the same latitudes, the depths of the highly saline lacustrine water column are insignificant. The article provides a review of the views of many authors on the genesis of tenises: L.S. Berg, Ya.S. Edelstein, A.S. Kes, K.N. Pestovsky, E.N. Posokhova, I.A. Volkov, who linked their origin with various exogenous processes: the remainder of the Oligocene sea or a huge ancient stream, the result of leaching of salts followed by compaction of rocks and deflation, inter-delta depressions, sor-deflation troughs, and others V.V. Goian (1968) for the first time came to the conclusion that tectonic processes are the main factors in the formation of the basins of shadows. The reconstruction of the buried topography according to drilling data confirmed the findings of V.V. Goian. The crystalline basement of the territory for the development of tenises is fragmented into separate blocks that have shifted relative to each other, and the basins of tenises are confined to tectonic depressions.